Factors Associated with Physical Aggression in Pregnant Women and Adverse Outcomes for the Newborn - Elaine Fernandes Viellas; Silvana Granado Nogueira da Gama; Márcia Lazaro de Carvalho; Liana Wernersbach Pinto (Brazilian Society of Pediatrics, 2013)
Objective: To assess the socioeconomic, demographic, and reproductive factors associated with physical aggression during pregnancy, and the negative outcomes for the newborn in two groups of women: adolescents and young adults. Method: Cross-sectional study with a sample of 8,961 mothers who were admitted to hospitals of the city of Rio de Janeiro during delivery. To test the hypothesis of homogeneity of proportions, the chi-squared test was used. Odds ratio and confidence intervals were estimated using logistic regression. Results: 5.0% of the adolescents and 2.5% of the young adult women suffered physical violence during pregnancy. In both groups, the variables associated with physical abuse were lower educational level, lower support from the child's father, and more attempts to interrupt the pregnancy. The increase in alcohol consumption was associated with physical abuse only in the group of adolescents; illicit drug use was only associated with physical abuse in young adults. The children of abused mothers had a two-fold increased chance of neonatal death, and a three-fold increased chance of post-neonatal death. Conversely, good quality prenatal care reduced the chance of physical aggression during pregnancy. Conclusions: The results emphasize the increased chance of neonatal and post-neonatal mortality among children of victims of physical abuse during pregnancy, and indicate the importance of prenatal care to identify women at higher risk of suffering aggression, the appropriate time to provide measures of protection and care for mother and baby.